Beyond the Migrant "Problem": Visualizing Global Migration. (September 2019) - Risam, Roopika
An area that has received comparatively little attention, in both postcolonial digital humanities and its overlap with studies of media and migration, is how geo-spatial data visualizations contribute to the othering of the migrant and how they can be used, in turn, to challenge the instantiation of the migrant as a "problem." Positioning data visualizations of migration as a narrative genre, this article considers how data visualizations of migration reinforce the trope of migrant-as-problem and how they might resist this inscription. Through multimodal rhetorical analysis of data visualizations of migration, I examine the interplay of written-linguistic, visual, and spatial modes of communication deployed in two approaches to visualizing migration and propose that the contexts of collaboration behind their composition influence their representation of the migrant as a "problem" and hold the power to resist this narrative.